PENGARUH PENGGUNAAN STRATEGI INKUIRI BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS BERITA SISWA KELAS VIII SMP NEGERI 2 BATANG KAPAS - Mandasari, Dona Gusnarida; Thahar, Harris Effendi; Noveria, Ena (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2016)
ABSTRACT  This study aims to (1) describe the level of skills of writing news eighth grade students of SMP Negeri 2 Batang Kapas without using a strategy of inquiry assisted audiovisual media, (2) describe the level of skills of writing news eighth grade students of SMP Negeri 2 Trunk Cotton using a strategy of inquiry assisted media audiovisual, and (3) describe the effect of the use of inquiry strategies aided audiovisual media to news writing skills of eighth grade students of SMP Negeri 2 Batang Kapas. This research is a quantitative study with experimental method. The results of this study there are three, namely (1) news writing skills without the use of audiovisual media strategy aided inquiry eighth grade students of SMP Negeri 2 Rod Cotton is the qualification More than Enough (LDC) with an average value of 68.37. (2) news writing skills using audiovisual media strategy aided inquiry eighth grade students of SMP Negeri 2 Cotton Trunk is qualifiers Good (B) with an average value of 81.63. (3) based on the t-test, the alternative hypothesis (H1) is accepted at 95% significance level and degrees of freedom (df) = (n1 + n2) -2 because thitung¬> ttable (12.27> 1.67). From the results of hypothesis testing there is a significant influence on news writing skills using audiovisual media strategy aided inquiry eighth grade students of SMP Negeri 2 Batang Kapas.  Kata kunci: Pengaruh, strategi inkuiri, mdi audiovisual, menulis berita